Instant and short-term effects of acupuncture for depression and anxiety in unstable angina pectoris patients with percutaneous coronary interventions - Pei, Juan Hui; Gan, Feng; Bai, Yun He; Xing, Yan Lin; Jia, Jian Jun; Wang, Huan (Frontiers in Cardiovascular Medicine, 2024)
Aims: Patients with unstable angina pectoris (UAP) usually present anxiety or depression during percutaneous coronary intervention (PCI). This study is sought to investigate the instant and short-term effects of acupuncture for anxiety and depression in UAP patients with PCI. Methods: 210 UAP patients who underwent PCI were recruited and randomly assigned (1:1:1) to acupuncture, placebo or control. Enzyme linked immunosorbent assay (ELISA) was used to detect fasting glucose, fasting insulin, Homeostasis model assessment of insulin resistance (HOMA-IR), Interleukin-6 (IL-6) , High-sensitivity C-reactive protein (Hs-CRP), Advanced oxidation protein products ( AoPPs ) and Oxidized Low Density Lipoprotein (OX-LDL). Serial questionnaires with the Hamilton Anxiety Scale (HAMA) and the Pittsburgh sleep quality index (PSQI) were evaluated, and heart rate variability (HRV) indicators were obtained. Results: Primary end-point: low frequency (LF)/high frequency (HF) was lower in the electroacupuncture group (p=0.014); while standard deviation of normalto-normal intervals (SDNN), average standard deviation of NN intervals((SDANN)), percentage of successive intervals that differs more than 50ms (PNN50) and HF were increased with acupuncture (p=0.018; p=0.043; p=0.016; p=0.002, respectively).Secondary end-point: Significant improvements in anxiety levels (HAMA) were observed in the three groups (p<0.001). The fasting insulin and HOMA-IR were similar between the control group and the acupuncture group (p=0.285; p=0.165, respectively).The levels of IL-6 and AoPPs distinguished among the three groups(p=0.021; p<0.001, respectively ) . However, no significant differences were found in fasting plasma glucose, fasting c-peptide, Hs-CRP and OX-LDL among the three groups (p=0. 585; p=0.611; p=0.902; p=0.756, respectively). Conclusions: In this study, short-term acupuncture may potentially relieve clinical symptoms before PCI treatment.